Oregano (Origanium Vulgare) Extract for Food Preservation and Improving Gastrointestinal Health - Jacob, P. Veenstra; Jeremy, J. Johnson (International Journal of Nutrition, 2019)
The Mediterranean diet has long been known to provide a variety of health benefits including cardiovascular protection, cancer prevention, and lowering gastrointestinal inflammation. Oregano (Origanium vulgare) is an herb prominent in the Mediterranean diet, and has been shown to possess several bioactive properties including anti-oxidant, anti-microbial, anti-inflammatory, and analgesic properties. The anti-oxidant and anti-microbial properties of oregano also make it a strong candidate as a natural food preservative. Because of the recent public concern with synthetic food preservatives, natural alternatives are increasingly being evaluated for effective food preservation. Oregano extract (OE) and essential oil (OEO) are two such agents that have shown promise as natural food preservatives. Additionally, oregano is being evaluated for its positive effect on gastrointestinal health, suggesting an additional benefit of food preservation with oregano. This review will describe in vitro studies related to the anti-microbial and anti-oxidant properties of oregano along with food preservation studies with oregano in various model food matrices. The major phytochemical content reported for OE and OEO will also be outlined to highlight the importance of characterizing the extract that is used, since the extraction process can have a significant effect on the phytochemicals therein. Finally, in vivo studies that investigate the gastrointestinal health benefits of oregano, specifically against inflammation, will be addressed to describe the role of oregano on gastrointestinal health.
Keywords: carvacrol; phytochemical; anti-microbial; anti-oxidant; food preservative; Origanum vulgare; oregano; thymol.